Relationship Between Fat-to-Muscle Ratio and Nonalcoholic Fatty Liver Disease in Middle-Aged and Older Adults with Type 2 Diabetes: Cross-Sectional Study - Zhang L; Sun Y; Zhao Y; Wu X; Han X (Diabetes, Metabolic Syndrome and Obesity)
Lei Zhang,1,2 Yulu Sun,1,2 Yiran Zhao,1,2 Xin Wu,1,2 Xiaofang Han1,2 1Department of Endocrinology, The Second People’s Hospital of Hefei, Hefei Hospital Affiliated to Anhui Medical University, Hefei, Anhui, 230011, People’s Republic of China; 2The Fifth Clinical School of Medicine, Anhui Medical University, Hefei, Anhui, 230032, People’s Republic of ChinaCorrespondence: Xiaofang Han, Email hxfanghf@sina.comPurpose: The fat-to-muscle mass ratio (FMR) is an innovative metric that integrates fat and muscle constituents. The aim of this study was to examine the efficacy of FMR in predicting non-alcoholic fatty liver disease (NAFLD) in individuals with T2DM.Methods: This cross-sectional study enrolled 307 hospitalized patients aged 50 years and older with T2DM. NAFLD was identified during ultrasound examination. Fat mass and muscle mass were quantified using dual-energy X-ray absorptiometry (DXA), with FMR calculated as fat mass (kg) divided by muscle mass (kg).Results: FMR was markedly elevated in the NAFLD patient group compared to the healthy control group (p< 0.001). Sex-specific analysis demonstrated notable sex differences in the diagnostic efficacy of this indicator for fatty liver: the area under the curve (AUC) of the subject’s work characteristics was significantly greater in females compared to males (0.860 vs 0.805), and the optimal threshold was also significantly elevated in females relative to males (0.563 vs 0.363). FMR was established as an independent predictor of fatty liver through multifactorial regression modeling, revealing a risk ratio of 28.171 (95% CI 7.008– 113.248, p< 0.001) in males, while the risk ratio for females was 3.259 (95% CI 1.221– 8.700, p=0.018), indicating higher predictive value in males.Conclusions: FMR was significantly and independently linked to an increased risk of NAFLD in middle-aged and elderly individuals with T2DM, a discovery that underpins the rationale for enhancing targeted interventions and prognostic management for patients with diabetes mellitus and fatty liver disease.Keywords: type 2 diabetes mellitus, fat-to-muscle ratio, non-alcoholic fatty liver disease, body composition